2013
DOI: 10.7763/ijapm.2013.v3.212
|View full text |Cite
|
Sign up to set email alerts
|

A Second Order Finite Difference Approximation for the Fractional Diffusion Equation

Abstract: Abstract-We consider an approximation of one-dimensional fractional diffusion equation. We claim and show that the finite difference approximation obtained from the Grünwald-Letnikov formulation, often claimed to be of first order accuracy, is in fact a second order approximation of the fractional derivative at a point away from the grid points. We use this fact to device a second order accurate finite difference approximation for the fractional diffusion equation. The proposed method is also shown to be uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…Generally speaking, if c −1 = c 1 it is hard/impossible to get a high order scheme for (1) with K 1 K 2 = 0. However, for second order approximations, as do in [20], we can firstly plug (12) into the two-sided problem (1), and then expand ∂u(x+βh,t) ∂t in Taylor's series w.r.t x, similar to the way of getting (23), (24) and (28). That is,…”
Section: Derivation Of the General Numerical Schemementioning
confidence: 99%
See 4 more Smart Citations
“…Generally speaking, if c −1 = c 1 it is hard/impossible to get a high order scheme for (1) with K 1 K 2 = 0. However, for second order approximations, as do in [20], we can firstly plug (12) into the two-sided problem (1), and then expand ∂u(x+βh,t) ∂t in Taylor's series w.r.t x, similar to the way of getting (23), (24) and (28). That is,…”
Section: Derivation Of the General Numerical Schemementioning
confidence: 99%
“…In [20,22], it is found that the Grünwald approximation has a superconvergent point. Based on this fact, in this subsection we derive a series of second order quasi-compact approximations for the combined left Riemann-Liouville fractional derivatives.…”
Section: Some Of the Second Order Approximationsmentioning
confidence: 99%
See 3 more Smart Citations